MAKNA UJARAN KALIMAT DOA NABI AYYUB AS DALAM AL-QUR’AN (ANALISIS SEMANTIK MODUS DAN FUNGSI KALIMAT QS. Al-ANBIYA:83 DAN QS. SHAD:41) - Abdul Gani, Ruslan (LPPM STAI Al-Azhary Cianjur, 2023)
Correct knowledge about the mode and function of a sentence determines whether or not a person understands the meaning of the message and idea to be conveyed in a sentence utterance. Moreover, for example, this sentence is part of the Qur'an which requires every Muslim to practice the ideas and messages contained in it in life. Researchers are interested in revealing one form of sentence utterance in the Qur'an and its function. The utterance is in the form of a prayer sentence from the Prophet Ayyub As in the QS. al Anbiya :83 and QS. Shad: 41. The research results show that the sentence mode used is declarative with an imperative function.